(untitled) (Jurnal Destinasi Pariwisata, 2025)
Bali’s rapidly expanding night-time economy increasingly intersects with the island’s customary life, raising questions about how nightlife tourism reshapes tradition. This study investigates the case of Berawa Traditional Village, Badung, which has transformed over the past decade from a quiet coastal settlement into a global nightlife hub anchored by international beach clubs. Employing a qualitative case study approach, data were collected through non-participant observation, in-depth interviews with community leaders and tourism actors, and document review. Analysis followed iterative narrative techniques to map the nightlife landscape and trace its cultural implications. Findings reveal a paradox: nightlife tourism generates employment, stimulates household income, and attracts international visitors, yet simultaneously produces vulnerabilities. These include economic dependency, widening social gaps, shifting social rhythms toward late-night activity, and declining youth engagement in rituals. Conflicts of sacred time and space emerge when temple ceremonies coincide with events, exemplified by a fireworks party that disrupted a Hindu ritual. Physical externalities, noise, glare, traffic, and waste. Further erode residents’ comfort and undermine ritual sanctity. Despite these pressures, the community demonstrates resilience through adat regulations, dialogue with venue operators, and multi-stakeholder coordination with government actors. The study underscores the urgency of culture-sensitive governance to safeguard traditions while sustaining economic benefits. Recommended measures include zoning and buffer areas around sacred sites, enforceable operating-hour and noise restrictions synchronized with the ritual calendar, strengthened community monitoring and benefit-sharing schemes, and visitor education programs that foreground Balinese values. Overall, Berawa’s experience illustrates the delicate balance between global nightlife industries and the sustainability of local cultural identity